1995
DOI: 10.1203/00006450-199507000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dopaminergic Control of Circulating Melanocyte-Stimulating Hormone-Related Peptides at Puberty

Abstract: Desacetyl a-melanocyte-stimulating hormone (MSH) (ACTH 1-13) is the main form of immunoreactive a-MSH circulating in human plasma. This study evaluates the possibility that a dopaminergic inhibitory mechanism could be operative during human development. Thus, a-MSH and ACTH 1-13 plasma levels were measured after dopaminergic blockade (domperidone (0.3 m a g body weight, maximum 10 mg, p.0.) in 13 prepubertal (aged 4.5-12.3 y) and 12 pubertal (aged 10.2-16.9 y) children. Both peptides were measured by RIA after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The use of a dopaminergic antagonist provided indirect evidence for active zona intermedia-like cells in prepubertal children, as it resulted in a significant increase in plasma α-MSHlike concentrations but not in post-pubertal controls. The elution position on HPLC suggested that the immunoreactive material was mainly desacetyl α-MSH (Facchinetti et al 1995). Desacetyl α-MSH does stimulate adrenal steroidogenesis, albeit at high concentrations, but its secretion would be accompanied by significant concentrations of other potential biologically active intermedia-like processed POMC peptides, e.g.…”
Section: The Human Pituitary Zona Intermedia the Adrenal Foetal Zonementioning
confidence: 99%
“…The use of a dopaminergic antagonist provided indirect evidence for active zona intermedia-like cells in prepubertal children, as it resulted in a significant increase in plasma α-MSHlike concentrations but not in post-pubertal controls. The elution position on HPLC suggested that the immunoreactive material was mainly desacetyl α-MSH (Facchinetti et al 1995). Desacetyl α-MSH does stimulate adrenal steroidogenesis, albeit at high concentrations, but its secretion would be accompanied by significant concentrations of other potential biologically active intermedia-like processed POMC peptides, e.g.…”
Section: The Human Pituitary Zona Intermedia the Adrenal Foetal Zonementioning
confidence: 99%
“…I N CONTRAST TO the majority of ␣-MSH produced by pituitary melanotrophs, desacetyl-␣-MSH is the predominant form of ACTH 1-13 NH 2 produced in the brain (1,2), the fetus (3,4), human blood (5), and amniotic fluid (6). Desacetyl-␣-MSH may also be more abundant than ␣-MSH in the pituitary of the A vy yellow mouse (7).…”
mentioning
confidence: 99%
“…NH 2 -terminal acetylation of desacetyl ␣-MSH to form ␣-MSH occurs in secretory vesicles just prior to exocytosis (42,66), but not all desacetyl ␣-MSH is acetylated, since desacetyl ␣-MSH is present in the circulation and brain of rodents and humans. The major form of plasma immunoreactive MSH is ␣-MSH in rodents and desacetyl ␣-MSH in humans (22,40), and the relative abundance of these two MSH peptides is developmentally regulated (11,23). Desacetyl ␣-MSH predominates in rodent and human brains and fetuses (23,54).…”
mentioning
confidence: 99%